2008
DOI: 10.1016/j.addbeh.2008.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Distress tolerance and pre-smoking treatment attrition: Examination of moderating relationships

Abstract: This study focused on the understudied group of smokers who commit to a smoking research study and then subsequently drop out before completing even one session of treatment (pre-inclusion attrition). This is an important group typically not examined in their own right, leaving little knowledge about the characteristics that differentiate them from those who complete treatment. As an initial investigation, the current study examined affective risk factors for attrition in a sample of 53 adults (79% African Ame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 43 publications
1
53
3
Order By: Relevance
“…Brandon et al (2003) found coeffi cient α to be .92 for the mirror-tracing task. A computerized version of this procedure is also available (e.g., Daughters et al, 2005;MacPherson et al, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…Brandon et al (2003) found coeffi cient α to be .92 for the mirror-tracing task. A computerized version of this procedure is also available (e.g., Daughters et al, 2005;MacPherson et al, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…Attrition is a critical problem in clinical trials for substance use and dependence; high attrition rates are commonplace and often expected. 37,[61][62][63] Pretreatment attrition among smokers has begun to receive attention only recently. 61,63 Factors associated with early attrition include younger age, lower socioeconomic status, and history of psychotropic medication use.…”
Section: Smoking Cessation/exercise Improve Cvd Biomarkersmentioning
confidence: 99%
“…37,[61][62][63] Pretreatment attrition among smokers has begun to receive attention only recently. 61,63 Factors associated with early attrition include younger age, lower socioeconomic status, and history of psychotropic medication use. Low motivation, weight concerns, and affective vulnerabilities, such as depression, also have been reported to predict early attrition.…”
Section: Smoking Cessation/exercise Improve Cvd Biomarkersmentioning
confidence: 99%
“…Thus, the primary dependent measure of the PASAT-C may have provided insufficient variability to detect relations between behavioral distress tolerance and other dependent measures such as delay discounting. Alternatively, behavioral measures of psychological distress tolerance such as the PASAT-C tend to significantly correlate with behavioral outcomes (e.g., dropout from treatment; MacPherson et al, 2008) but not selfreported behaviors (e.g., motivations for drug use). Future studies should explore the relation between persistence in the PASAT-C and degree of opportunity-cost delay discounting when real rewards and delays are arranged.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…For instance, individuals with low levels of distress tolerance exhibit shorter durations of smoking abstinence (Brown, Lejuez, Kahler, Strong, & Zvolensky, 2005;, and tend to drop out of substance abuse treatment early (Daughters, Lejuez, Bornovalova, et al, 2005;MacPherson, Stipelman, Duplinsky, Brown, & Lejuez, 2008). Likewise, self-reported distress tolerance is related to self-reported substance-use frequency and/or duration of drug use and self-reported problems associated with drug use (e.g., Buckner, Keough, & Schmidt, 2007;Howell, Leyro, Hogan, Buckner, & Zvolensky, 2010).…”
mentioning
confidence: 99%